'Cet autre moy': Poetic Selves and Anterotic Friendships in Sixteenth-Century France. Issue 1 (2nd January 2020) - Fallanca, Vittoria
Abstract : This article begins by considering a Complainte by the poet Philippe Desportes (1581) which contains the first recorded use of the substantive 'self' in French ('cet autre moy'). Following Terence Cave (1999), it highlights the fact that it occurs in the context of Renaissance writings on friendship predominantly influenced by the 'Aristotelian-Ciceronian model'. It proposes that alongside this well-established model of friendship, there is another, competing model, what it terms the 'anterotic' model based on the mythological figure of Anteros. The anterotic model is rooted in strife as well as mutuality, and evocatively captures the dynamics of the creation of poetic identity in sixteenth-century French writings, including the fraught relationship between poet and verse, and the struggle between originality, emulation and independence. Seen against this backdrop, the substantive 'self' reflects not so much 'modern' identity as we know it, but a poetic identity encapsulated in the complex doubleness of Anteros.